2011
DOI: 10.1038/modpathol.2011.92
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical algorithm for differentiation of lung adenocarcinoma and squamous cell carcinoma based on large series of whole-tissue sections with validation in small specimens

Abstract: Immunohistochemistry is increasingly utilized to differentiate lung adenocarcinoma and squamous cell carcinoma. However, detailed analysis of coexpression profiles of commonly used markers in large series of whole-tissue sections is lacking. Furthermore, the optimal diagnostic algorithm, particularly the minimalmarker combination, is not firmly established. We therefore studied whole-tissue sections of resected adenocarcinoma and squamous cell carcinoma (n ¼ 315) with markers commonly used to identify adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
279
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(303 citation statements)
references
References 45 publications
16
279
1
1
Order By: Relevance
“…However, recent immunohistochemical studies that have focused on poorly differentiated non-small cell carcinomas in small biopsies or cytology specimens with resected tumors as the gold standard have shown that some markers, especially when used in combination, are indeed useful and accurate in subclassifying poorly differentiated non-small cell lung carcinomas. [5][6][7][8] As subclassification using these markers shows excellent correlation with the gold standard H&E-based diagnosis on resected tumors, immunohistochemistry has become accepted as a reliable technique for subclassification when diagnostic features on H&E morphology are absent in a small biopsy. To summarize the current state of non-small cell lung carcinoma subclassification, H&E-based criteria remain the gold standard for subclassifying resected tumors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent immunohistochemical studies that have focused on poorly differentiated non-small cell carcinomas in small biopsies or cytology specimens with resected tumors as the gold standard have shown that some markers, especially when used in combination, are indeed useful and accurate in subclassifying poorly differentiated non-small cell lung carcinomas. [5][6][7][8] As subclassification using these markers shows excellent correlation with the gold standard H&E-based diagnosis on resected tumors, immunohistochemistry has become accepted as a reliable technique for subclassification when diagnostic features on H&E morphology are absent in a small biopsy. To summarize the current state of non-small cell lung carcinoma subclassification, H&E-based criteria remain the gold standard for subclassifying resected tumors.…”
mentioning
confidence: 99%
“…Similarly, although p63 is more sensitive for squamous cell carcinomas than CK5/6, the latter is useful when p63 staining is focal, weak or equivocal. 7 In samples for which cellularity is very low, it has been suggested that a more limited panel composed of TTF-1 and p63 can be used in most cases to conserve the tissue in the event that it is required for molecular studies. 7 Similar concerns have been cited by a consensus panel in recommending that the panel be limited to TTF-1 and p63, with or without a mucin stain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…71 However, LUAD and LUSC also differ at the molecular level. For example, activating mutations in tyrosine kinase signaling pathway genes (e.g., EGFR, ALK, RET, ERBB2) are common in LUAD, while NFE2L2 mutations are a distinguishing feature of LUSC.…”
Section: Clear Cell Renal Carcinomamentioning
confidence: 99%